A Comprehensive Evaluation of the Existing Approaches for Controlling and Managing the Proliferation of Water Hyacinth (Eichhornia crassipes): Review - Karouach, Fadoua; Ben Bakrim, Widad; Ezzariai, Amine; Sobeh, Mansour; Kibret, Mulugeta; Yasri, Abdelaziz; Hafidi, Mohamed; Kouisni, Lamfeddal (Frontiers in Environmental Science, 2022)
Several countries, suffer economically from the impacts of water hyacinth (WH). Although the plant causes a huge loss of biodiversity resources, it can provide multitude of compounds with marked beneficial applications. The present review describes the existing solutions for managing and controlling the WH plant worldwide and the initiatives adopted by some countries, regarding the implementation of control programs to mitigate the impact of WH. In fact, bibliographic research on large scale applications to control WH in 26 countries was comprehensively reviewed. Moreover, a descriptive analysis was done to clearly visualize the most cost-effective control methods. Results showed that an integrated approach, with a combination of biological and physical control methods, is the most cost-effective method. Short/medium physical control promptly manages the plant’s proliferation and thus complements the effect of biological control. An integrated ‘’Biological-physical-chemical’’ control is also recommended. The application of herbicides can be considered under some specific conditions.